2010
DOI: 10.1111/j.1095-8339.2010.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics and classification of the pantropical fern family Lindsaeaceae

Abstract: The classification and generic definition in the tropical-subtropical fern family Lindsaeaceae have been uncertain and have so far been based on morphological characters only. We have now studied the evolutionary history of the Lindsaeaceae by simultaneously optimizing 55 morphological characters, two plastid genes (rpoC1 and rps4) and three non-coding plastid intergenic spacers (trnL-F, rps4-trnS and trnH-psbA). Our data set included all genera associated with Lindsaeaceae, except Xyropteris, and c. 73% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 145 publications
3
58
1
4
Order By: Relevance
“…é uma família monofilética, com sete gêneros e cerca de 234 espécies (PPG I 2016), possui distribuição pantropical, com algumas espécies estendendo-se à regiões subtropicais na América do Sul, leste da Ásia e Nova Zelândia (Lehtonen et al 2010). São plantas terrícolas ou menos comumente rupícolas; caule curto a longo-reptante, geralmente protostélico, ocasionalmente solenostélico, com escamas ou tricomas; lâmina 1-3-pinada ou mais decomposta, quase sempre glabra; venação geralmente livre, eventualmente anastomosada; soros marginais ou submarginais, com indúsio extrorso (Smith et al 2006).…”
Section: Lindsaeaceaeunclassified
See 1 more Smart Citation
“…é uma família monofilética, com sete gêneros e cerca de 234 espécies (PPG I 2016), possui distribuição pantropical, com algumas espécies estendendo-se à regiões subtropicais na América do Sul, leste da Ásia e Nova Zelândia (Lehtonen et al 2010). São plantas terrícolas ou menos comumente rupícolas; caule curto a longo-reptante, geralmente protostélico, ocasionalmente solenostélico, com escamas ou tricomas; lâmina 1-3-pinada ou mais decomposta, quase sempre glabra; venação geralmente livre, eventualmente anastomosada; soros marginais ou submarginais, com indúsio extrorso (Smith et al 2006).…”
Section: Lindsaeaceaeunclassified
“…Gênero pantropical, monofilético (Lehtonen et al 2010), com cerca de 180 espécies (PPG I 2016). Das 30 espécies conhecidas no Brasil, 25 ocorrem na região norte do país (Prado et al 2015).…”
Section: Lindsaeaceaeunclassified
“…These species also share a short, typically uninerval, sori. Odontosoria chinensis and O. biflora were resolved as sister species pair in the cladistic analysis, but the phylogenetic relationships of O. quadripinnata and O. veitchii remain uncertain, due to the lack of molecular data (Lehtonen et al 2010). However, it is probable that all Odontosoria species with monolete spores are closely related.…”
Section: Odontosoria Quadripinnatamentioning
confidence: 99%
“…Recent studies on Lindsaeaceae systematics (Lehtonen et al 2010) revealed two collections of a morphologically unusual Odontosoria from New Guinea. These specimens probably represent the 'quadripinnate form' of Sphenomeris retusa (Cav.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation